2010
DOI: 10.1038/ajg.2010.273
|View full text |Cite
|
Sign up to set email alerts
|

Live Image Processing Does Not Increase Adenoma Detection Rate During Colonoscopy: A Randomized Comparison Between FICE and Conventional Imaging (Berlin Colonoscopy Project 5, BECOP-5)

Abstract: This large randomized trial could not show any objective advantage of the FICE technique over conventional high-resolution endoscopy in terms of improved ADR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(56 citation statements)
references
References 17 publications
1
45
1
3
Order By: Relevance
“…A study examining the impact of FICE in combination acetic acid in Barrett's esophagus proved a modest improvement in high-grade dysplasia detection compared to random biopsies [23]. Two large studies have shown that there is no additive benefit for the use of FICE in colorectal adenoma detection [24,25]. While characterization of colonic polyps reaches 87% when FICE with magnification is used [26].…”
Section: Clinical Applicabilitymentioning
confidence: 97%
“…A study examining the impact of FICE in combination acetic acid in Barrett's esophagus proved a modest improvement in high-grade dysplasia detection compared to random biopsies [23]. Two large studies have shown that there is no additive benefit for the use of FICE in colorectal adenoma detection [24,25]. While characterization of colonic polyps reaches 87% when FICE with magnification is used [26].…”
Section: Clinical Applicabilitymentioning
confidence: 97%
“…Results of cap-fitted colonoscopy have been mixed [75][76][77][78]. Electronic highlighting strategies such as narrow band imaging [79][80][81][82][83][84], the Fujinon Intelligent ChromoEndoscopy System [85][86][87], and the Pentax i-scan System [88] have either been ineffective [80-83, 85, 86], had unconvincing study designs [84], or very low level adenoma detection in control groups [88]. Pancolonic chromoendoscopy is effective in improving the detection of diminutive adenomas [89] but adds time and inefficiency to procedure performance.…”
Section: Withdrawal Techniquementioning
confidence: 99%
“…Furthermore, because of its variable setting functions (up to 10), the operator has flexibility in selection of the most suitable wavelengths for each examination. Although some randomized controlled trials have been conducted (Aminalai et al, 2010Chung et al, 2010, no one has yet demonstrated improvement in adenoma miss or detection rates compared with WLI. Autofluorescence imaging is an endoscopic technique for visualizing with reflected autofluorescence, which is emitted from an endogeneous fluorophore by exposing it to short wavelength excitation light (Fig.…”
Section: Optical Methods For Minimizing the Overlooking Of Colorectalmentioning
confidence: 99%